Replacement of lime with industrial wastes in hot metal desulfurization mixtures - Santo E.V.D.E.; Soares S.G.; de Oliveira H.C.C.; Junca E.; Grillo F.F.; de Oliveira J.R. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The steel production enhancement in recent decades has increased the solid waste generation in the steel plants. Due to the increase in the environmental policies stringency, efforts have been made to give them a more appropriate destination. In this context, the internal reuse of these materials is a solution often applied by the industry to reduce production costs and to decrease slag generation. Therefore, the aim of this research is to replace calcitic lime by limestone waste and KR slag in hot metal desulfurization, which are wastes from steel production. The KR slag is the waste generated by the desulfurization process in Kambara Reactor. Experimental desulfurization tests were carried out in a resistance furnace at a temperature of 1350°C, in an inert atmosphere with constant stirring of 500 rpm. Along with the tests, simulations were carried out with FactSage 7.0 software in order to obtain the phases present in each mixture at the working temperature and compare them with the practical results. It was found that the tricalcium silicate phase (3CaO·SiO2) was present in mixtures with lower desulfurization efficiency, which shows its kinetic limitation. The use of limestone waste proved to be more efficient than the use of KR slag.